2009
DOI: 10.1111/j.1440-1584.2009.01106.x
|View full text |Cite
|
Sign up to set email alerts
|

Mapping oncology services in regional and rural Australia

Abstract: Survey data highlight marked cancer service deficiencies in rural and regional Australia. It is not unreasonable to conclude that these deficiencies might contribute to poorer outcomes for cancer patients living in these areas. The results suggest the need for short- and long-term measures to improve access to best-practice cancer services for patients living in regional, rural and remote areas of Australia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
98
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 82 publications
(99 citation statements)
references
References 28 publications
(32 reference statements)
1
98
0
Order By: Relevance
“…A review of rural and regional cancer services reported over half of participating cancer services identified an urgent need for improving psychosocial services [37]. Our sample population were all recruited from the metropolitan district; therefore caution is required when extrapolating these findings to the rural community.…”
Section: Discussionmentioning
confidence: 96%
“…A review of rural and regional cancer services reported over half of participating cancer services identified an urgent need for improving psychosocial services [37]. Our sample population were all recruited from the metropolitan district; therefore caution is required when extrapolating these findings to the rural community.…”
Section: Discussionmentioning
confidence: 96%
“…However, given that urban-rural inequality in survival was evident only among women diagnosed with non-localised breast cancer it seems more likely that not receiving stage-appropriate therapy may be the underlying reason for these findings. Again this may be related to geographic distances and oncology service location [20].…”
Section: Discussionmentioning
confidence: 99%
“…A mapping survey by Clinical Oncology Society of Australia concluded that there are deficiencies and variations in care exist between states and between the regional and rural sites and the metropolitan sites benchmarked. 10 Variations of care highlighted included the ordering of chemotherapy by a nonmedical oncologist, the administration of chemotherapy by a non-oncology certified chemotherapy nurse and the lack of availability of cytotoxic administration guidelines. Other barriers include travel distance for regular monitoring, the cost of travel, the length of stay away from home, the need for friends or family to accompany them and look after their properties or businesses while they are away.…”
Section: Introductionmentioning
confidence: 99%